Estudio de los hongos de la Reserva de la Biósfera El Cielo, Tamaulipas. Consideraciones sobre la distribución y ecología de algunas especies - Heredia, Gabriela (Instituto de Ecología, A.C., 1989)
Th distribution, substrate and importance of 126 species of fungi collected along and altitudinal gradient in the Biosphere Reserve El Cielo in Tamaulipas, Mexico, are discussed. Surveys were carried out in 4 different plant communities: semi-evergreen seasonall forest, cloud forest, oak-pine forest, and a transitional area between the cloud forest and the oak-pine forest. The mycofloristic list includes 5 Myxomycetes, 19 Ascomycetes, and 102 Basidiomycetes.